Modeling human gastrointestinal inflammatory diseases using microphysiological culture systems. (September 2014) - Hartman, Kira G; Bortner, James D; Falk, Gary W; Ginsberg, Gregory G; Jhala, Nirag; Yu, Jian; Martín, Martín G; Rustgi, Anil K; Lynch, John P
Gastrointestinal illnesses are a significant health burden for the US population, with 40 million office visits each year for gastrointestinal complaints and nearly 250, 000 deaths. Acute and chronic inflammations are a common element of many gastrointestinal diseases. Inflammatory processes may be initiated by a chemical injury (acid reflux in the esophagus), an infectious agent ( Helicobacter pylori infection in the stomach), autoimmune processes (graft versus host disease after bone marrow transplantation), or idiopathic (as in the case of inflammatory bowel diseases). Inflammation in these settings can contribute to acute complaints (pain, bleeding, obstruction, and diarrhea) as well as chronic sequelae including strictures and cancer. Research into the pathophysiology of these conditions has been limited by the availability of primary human tissues or appropriate animal models that attempt to physiologically model the human disease. With the many recent advances in tissue engineering and primary human cell culture systems, it is conceivable that these approaches can be adapted to develop novel human ex vivo systems that incorporate many human cell types to recapitulate in vivo growth and differentiation in inflammatory microphysiological environments. Such an advance in technology would improve our understanding of human disease progression and enhance our ability to test for disease prevention strategies and novel therapeutics. We will review current models for the inflammatory and immunological aspects of Barrett's esophagus, acute graft versus host disease, and inflammatory bowel disease and explore recent advances in culture methodologies that make these novel microphysiological research systems possible.